2020
DOI: 10.1080/2162402x.2020.1776058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pseudoprogression and treatment beyond progression on outcome in patients with non-small cell lung cancer treated with immune checkpoint inhibitors

Abstract: Background: Immune checkpoint inhibitors (ICI) have become an important treatment option for nonsmall cell lung cancer (NSCLC). We aimed to evaluate the clinical impact of pseudoprogression (PsP) and treatment beyond RECIST1.1-defined progressive disease (TBP) on outcome in NSCLC patients treated with ICI. Methods: NSCLC patients treated with ICI between Mar 2016 and July 2018 were recruited in a consecutive manner. Response was assessed every 8-12 weeks using RECIST1.1 and iRECIST. Based on iRECIST, PsP was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“… 1 However, atypical patterns of response, such as pseudoprogression and hyperprogressive disease (HPD), have been observed in cancers treated with ICIs. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“… 1 However, atypical patterns of response, such as pseudoprogression and hyperprogressive disease (HPD), have been observed in cancers treated with ICIs. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…The study search process is shown in Figure 1 . The characteristics of the 11 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] including 6210 patients are summarized in Table 1 . One study was a pooled analysis of individual patient data (IPD) from 14 Food and Drug Administration (FDA)-approved randomized controlld trials (RCTs), one was an RCT, one was a phase II clinical trial, and eight were observational studies (1 prospective study and 7 retrospective studies).…”
Section: Resultsmentioning
confidence: 99%
“…Although iRECIST captured the benefit of ICI treatment in a subset of patients which RECIST 1.1 did not, and significantly prolonged PFS compared to RECIST 1.1, the magnitude of benefit was modest (3.9% of patients with pseudoprogression and PFS prolongation by 0.46 months), and these results should be interpreted with caution concerning the benefit and drawbacks of iRECIST application in clinical trial and practice [ 20 , 23 ]. While the application of iRECIST is beneficial to fully investigate the atypical response such as pseudoprogression and treatment efficacy, it adds considerable burden in imaging interpretation, data management, statistical analysis, cost, and potential risk of maintaining futile treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations